Polymeric drugs and drug delivery systems : developed from a symposium sponsored by the Division of Polymer Chemistry, Inc. at the 200th National Meeting of the American Chemical Society, Washington, D.C., August 26-31, 1990 /: developed from a symposium sponsored by the Division of Polymer Chemistry, Inc. at the 200th National Meeting of the American Chemical Society, Washington, D.C., August 26-31, 1990. (2019) - Unknown
No abstract available